Development of Creative Abilities of Junior School Children in Reading Literacy Lessons (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The relevance and demand for the development of creative abilities of primary school students in reading literacy lessons is substantiated. The content of the combination “reading literacy” is revealed. The characteristics of the process of development of creative ability in primary school students are presented. A comparative analysis of the concepts “creativity” and “creativity” is proposed. Based on the analysis of scientific and methodological sources, an analysis of the concept of “creative ability” is given.